Export Diversification in Twelve European and Central Asian Countries and the Role of the Commodity Boom - Varela, Gonzalo J. (World Bank, Washington, DC, 2013)
This paper examines export diversification along the product and market dimensions for selected countries in the Europe and Central Asia region and, more generally, export performance. While the latter is extraordinary, with average export growth rates above 10 percent, the evidence on diversification is less impressive, and hints at a role played by the interaction of natural resource abundance and the commodity price boom. A cross-country analysis including 171 economies suggests that the region's resource rich countries are less diversified than would be expected given their resource endowments, level of development, and size. The commodity boom period was associated with an increase in concentration for the resource rich along the product dimension: they did not increase the number of products exported and became more reliant on oil and gas. During the same period, the resource poor increased their export product scope while maintaining other concentration indices unchanged. A similar but milder pattern is found for diversification along the destination dimension.